Targeting Multiple Mitochondrial Processes by a Metabolic Modulator Prevents Sarcopenia and Cognitive Decline in SAMP8 Mice - Brunetti, Dario; Bottani, Emanuela; Segala, Agnese; Marchet, Silvia; Rossi, Fabio; Orlando, Fiorenza; Malavolta, Marco; Carruba, Michele O.; Lamperti, Costanza; Provinciali, Mauro; Nisoli, Enzo; Valerio, Alessandra (Frontiers in Pharmacology, 2020)
The age-dependent decline of skeletal muscle and cognitive function often coexist in elderly subjects and share common pathophysiological mechanisms, including mitochondrial dysfunctions, which can prelude to overt sarcopenia and/or dementia. Dietary supplementation with formulations of essential and branched-chain amino acids (EAA-BCAA) is a promising preventive strategy because it can preserve mitochondrial biogenesis and function. The senescence-accelerated mouse-prone 8 (SAMP8) is considered an accurate model of age-related muscle and cognitive alterations. Hence, we aimed to investigate the progression of mitochondrial dysfunctions during muscle and cognitive aging of SAMP8 mice, as well as to study the effects of a novel EAA-BCAA-based metabolic modulator on these changes. We studied body condition, motor endurance, and working memory at 5, 9, 12, and 15 months of age. Parallel changes in protein levels of mitochondrial respiratory chain subunits, transcriptional regulators of mitochondrial biogenesis and dynamics, and the antioxidant response, as well as respiratory complex activities, were measured in the quadriceps femoris and the hippocampus. The same variables were assessed in 9-month-old SAMP8 mice that received dietary supplementation with the novel EAA-BCAA formulation, containing added tricarboxylic acid cycle intermediates and co-factors (PD-0E7, 1.5 mg/kg/body weight/day in drinking water) for 3 months. Contrary to untreated mice, showing significant molecular and phenotypic impairment, PD-0E7-treated mice showed preserved healthy body condition, muscle weight to body weight ratio, motor endurance, and working memory at 12 months of age. The PD-0E7 mixture increased the protein levels and the enzymatic activity of mitochondrial complex I, II, and IV and the expression of proliferator-activated receptor γ coactivator-1α, optic atrophy protein 1, and nuclear factor, erythroid 2 like 2 in muscles and hippocampus. The mitochondrial amyloid-β-degrading pitrilysin metallopeptidase 1 was upregulated, while amyloid precursor protein was reduced in the hippocampi of PD-0E7 treated mice. In conclusion we show that a dietary supplement tailored to boost mitochondrial respiration preserves skeletal muscle and hippocampal mitochondrial quality control and health. When administered at the early onset of age-related physical and cognitive decline, this novel metabolic inducer counteracts the deleterious effects of precocious aging in both domains.